Sentiment Analysis On The Reviews Of Civil Registration And Population Service Sub-District Of West Jakarta Using K-Nearest Neighbor Algorithm - Emil Salim; Mohammad Syafrullah (Universitas Budi Luhur, 2023)
Population administration plays an important role in Indonesia as it is involved in various activities. At the regional government level, the Population and Civil Registration Office is responsible for these matters. In West Jakarta, the Sub-district Population and Civil Registration Office is a government body that handles the technical aspects of population administration. Based on data from 2020, the population in West Jakarta reached 2,434,511 people. This office is responsible for providing services to the community, which involves various responses and opinions from the public. Some opinions are positive and constructive, while others may be dissatisfied with the services provided or have unmet expectations. This research aims to analyze public perspectives on the administration services of the Sub-district Population and Civil Registration Office in West Jakarta using machine learning approach, specifically the CountVectorizer feature extraction and K-Nearest Neighbor algorithm. The dataset used is sourced from an online form accessible by society. The analysis results from 386 reviews show that there are 311 (80.57%) positive reviews and 75 (19.43%) negative reviews, with the best testing performed using a K value of 3, achieving an accuracy rate of 83%, precision of 82%, and recall of 100%.